Analysis of fuel mixing in fluidized beds - Measurements with a hot camera probe in the Chalmers gasifier and 3D particle tracking in a cold flow model - Köhler, Anna (My University, 2015)
The present work describes a newly implemented 3D magnetic particle tracking system, which is tested in a fluidized bed down-scaled cold model. The method is used for experimental work with varying fluidization conditions, i.e. different superficial gas velocities, different pressure drops over the air distributor as well as different fixed bed heights. The measurement method obtains the motion of a single fuel particle at any time in the bubbling fluidized bed, which makes it possible to analyse the fuel mixing in fluidized beds. A method to calculate the lateral dispersion coefficient is developed. Further, the measurements of fuel dispersion in a hot industrial gasifier are described and results are compared with the values from the down-scaled model. The values show sufficient agreement. Analysis proves sufficient robustness of the measurement method and although the experiments are done with a single tracer particle the measurements give statistically expected distribution of many fuel particles moving in a fluidized bed. The presence of mixing cells and flow structures in a bubbling fluidized bed can be visualized in 3 dimensions, while the established bubble flows show expected trends like increasing size of bubble paths with increasing bed height and velocities.
Keywords: Energi; Hållbar utveckling; Energiteknik; Energy; Sustainable Development; Energy Engineering